Acoustic quality in times of pandemic: urban corridor with community green space. - Juarez, Isabel del Valle (2023)
In order to assess an acoustic environment in the face of the pandemic of the infectious virus COVID-19 detected for the first time in December 2019, the present work aims to identify and evaluate the acoustic behavior of an urban corridor with its community green space in the city of San Miguel de Tucumán, through the study of certain sound, environmental and social variables, in the context of Preventive and Compulsory Social Isolation (ASPO). The exploratory and descriptive, analytical-deductive and case study methods were adopted. Quantitative paradigms were used by means of surveys and sound measurements in 15 points determined in the sector with instruments according to regulations and qualitative paradigms, with surveys to users of those spaces. It was concluded that the noise levels obtained were higher than those recommended by the World Health Organization (WHO), even in the context of a health crisis and with activity restrictions.